Prompting ChatGPT: A Syntactic Analysis of English Education Students’ Queries at the University Level - Basith, Rayhan Izzati; Tathahira, Tathahira (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2025)
This study investigates the syntactic features of prompts formulated by English Education students at Syiah Kuala University when interacting with ChatGPT for academic purposes. Specifically, it examines sentence length, sentence form (imperative or interrogative), and grammatical accuracy in prompts related to the Morphology and Syntax course. Using a qualitative descriptive approach, data were collected from three students in semester six or above, each submitting five naturally composed prompts. The findings reveal a dominance of imperative sentences, with varying degrees of sentence length and grammatical correctness. While most prompts were structurally sound, occasional errors—particularly in complex constructions—highlighted syntactic challenges. The study provides insight into students’ linguistic competence in AI-assisted learning environments and emphasizes the need for further syntactic awareness in prompt engineering. These results contribute to growing discussions on digital literacy and the pedagogical implications of using generative AI in higher education.